Kinetic effects of thermal ions on internal kink modes in tokamak plasmas - Jiangyue Han; Yasushi Todo; Hao Wang; Masahiko Sato; Jialei Wang (Nuclear Fusion, 2025)
Linear growth of internal kink mode is investigated using a kinetic-MHD hybrid simulation model under realistic tokamak conditions. By comparing purely fluid (single-fluid MHD) simulations with kinetic thermal ion simulations using various coupling schemes, it is demonstrated that thermal-ion effects—including finite orbit width and ion pressure anisotropy—can significantly stabilize the internal kink mode. The maximum perturbation of distribution function aligns with resonance regions and near the passing-trapped boundary, indicating outward transport and redistribution of thermal ions. The net positive energy transfer from the mode to thermal ions leads to a reduction in growth rate. These results underscore the importance of incorporating thermal ion kinetics when modeling internal kink instabilities in fusion plasmas.